PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON ASSET PADA PT ULTRAJAYA MILK INDUSTRY DAN TRADING COMPANY, TBK PERIODE 2013-2022 - Devi Yunita; Zulfitra (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Current Ratio (CR) and Debt to Equity Ratio (DER) on Return on Asset (ROA) at PT Ultrajaya Milk Industry and Trading Company Tbk for the period 2013-2022 in the last 10 years partially and simultaneously. The research method uses a descriptive analysis method with a quantitative approach. The independent variables used in this study are Current Ratio and Debt to Equity Ratio while the dependent variable is Return on Asset. The population used in this study is all financial reports of PT Ultrajaya Milk Industry and Trading Company Tbk. The sample used is the balance sheet and profit and loss financial statements at PT Ultrajaya Milk Industry and Trading Company Tbk, with sampling in this study using the Purposive Sampling method. The data analysis techniques used are descriptive statistics, classical assumption test, correlation test, determination coefficient test, simple and multiple linear regression equations, t test and F test then this test uses SPSS 25. Based on the results of the t test shows that 1.679 t count value 1.679 <t table 2.364, it is concluded that the Current Ratio (X1) partially has no significant effect on Return On Asset (Y). Based on the results of the t test shows that the t count value of the Debt to Equity Ratio variable is 0.582. Because the t count value is 0.582> t table 2.364, there is a significant effect of Debt to Equity Ratio (X2) on Return On Asset (Y). Based on the results of the simultaneous F test count of 2.055 with a significant value of 0.015. the F table value is 4.35. So that the calculated F 2.055 > F table 4.35, then the Current Ratio (X1) and Debt to Equity Ratio (X2) have a simultaneous effect on Return On Asset (Y).